Perubahan Status Energi Pada Proses Reproduksi Induk Domba Garut Yang Diberi Pakan Komplit Berbasis Hijauan Sorgum dan Indigofera - Taufik Rizki Nurrochman; Aaf Falahudin; Rachmat Somanjaya (Tropical Livestock Science Journal, 2023)
Blood urea nitrogen (BUN) is an indicator of the efficiency of protein use in metabolism which is correlated with energy adequacy status. This study aimed to analyze and measure differences in energy adequacy status of arrowroot ewes in the premating, pregnancy, and lactation phases that were fed a complete diet of sorghum indigofera. The method used experimentally with Completely Randomized Design (CRD). There were 2 feed treatments, namely field grass (RL) as control and complete feed based on forage sorghum indigofera with a composition of 50% sorghum silage + 40% indigofera hay + 10% fine bran (SI) and repeated 14 times. The data obtained were analyzed using a two sample t-test. The results showed that there was a decrease in BUN in both treatments in each phase, but overall the average BUN value did not show a significant difference (P>0.05). Significant differences (P<0.05) only occurred at the beginning of pregnancy, mid and late lactation with BUN values of 21.18±1.04; 13.25±0.60; 15.18±0.67 for RL and 18, respectively. ,61±1.10; 15.86±0.82; 12.43±0.56 for SI. So it can be concluded that complete feed based on sorghum indigofera has the same energy change status as field grass, and in SI it can be used as a substitute for field grass.